2021
DOI: 10.1128/spectrum.00716-21
|View full text |Cite
|
Sign up to set email alerts
|

Biosafety and Proteome Profiles of Different Heat Inactivation Methods for Mycobacterium tuberculosis

Abstract: Inactivation of Mycobacterium tuberculosis is an important step to guarantee biosafety for subsequent M. tuberculosis identification and related research, notably in areas of endemicity with minimal resources. However, certain biomolecules might be denatured or hydrolyzed because of the harsh inactivation process, and a standardized protocol is yet to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…However, heat treatment has varying inactivation efficiencies, with some groups reporting uniform killing (Krugman 1975, Castro, Gonzalez et al 2009, and others raising issues with kill consistencies (Billard-Pomares, Bleibtreu et al 2019). Differences in temperature, duration and container type of heat inactivation has led to no uniform consensus being reached (Wang, Putri et al 2021). Ethanol can be used as a chemical inactivation method, with Dunne et al demonstrated that a ≥15minute incubation time was sufficient to inactivate a loop full of culture (Dunne, Doing et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, heat treatment has varying inactivation efficiencies, with some groups reporting uniform killing (Krugman 1975, Castro, Gonzalez et al 2009, and others raising issues with kill consistencies (Billard-Pomares, Bleibtreu et al 2019). Differences in temperature, duration and container type of heat inactivation has led to no uniform consensus being reached (Wang, Putri et al 2021). Ethanol can be used as a chemical inactivation method, with Dunne et al demonstrated that a ≥15minute incubation time was sufficient to inactivate a loop full of culture (Dunne, Doing et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…inactivation has led to no uniform consensus being reached(Wang, Putri et al 2021). Ethanol can be used as a chemical inactivation method, with Dunne et al demonstrated that a ≥15minute incubation time was sufficient to inactivate a loop full of culture(Dunne, Doing et al 2014).…”
mentioning
confidence: 99%
“…A sample inactivation step was performed to reduce the infection risk associated with clinical specimens that may contain MTB (17). Specimen material directly in contact with inactivation reagent (IR) for at least 1 hour was liqui ed and considered to have a reduced infection risk (18).…”
Section: Sample Size and Testing Proceduresmentioning
confidence: 99%